Typification of coffee growing in Temascaltepec, State of Mexico - Ramírez Dávila, José Francisco; Salgado Siclán, Martha Lidya; Partida Sedas, José Gervasio; Rubí Arriaga, Martín (Revista Mexicana de Ciencias Agrícolas, 2023)
In Mexico, coffee (Coffea arabica L.) is grown on 644 801 ha by 500 000 producers in 15 states. The State of Mexico with 539 ha ranks eleventh in volume of production, however, it meets conditions that place it among the first three places of the ‘The Cup of Excellence’ competition. With the aim of typifying coffee growing in the municipality of Temascaltepec, State of Mexico, during April and May 2021, 20 producers were interviewed, 19 questions related to sociodemographic, economic, agronomic and cultural aspects were considered. The age of the producer was (56.05 years), level of schooling (8.25 years), average yield per hectare (977.5 kg), planting density (869.5 plants ha-1), number of years growing coffee in the area (21.85 years), international selling price ($525.00), as ground coffee, income from the sale of cherry coffee ($9 713.35). The principal component analysis grouped the highest percentage of variability in the first two components (46.5%) and allowed the identification of three groups of growers: high, medium and low profitability.
Keywords: Coffea arabica L; coffee grower; productivity; sociodemographic